1999
DOI: 10.1093/carcin/20.12.2261
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increased vegetable and fruit consumption on markers of oxidative cellular damage

Abstract: The goal of this study was to test the hypothesis that increased consumption of vegetables and fruit would reduce markers of oxidative cellular damage that can be assessed in blood or urine. Twenty-eight women participated in a 14 day dietary intervention. The primary end-points assessed were: 8-hydroxydeoxyguanosine (8-OHdG) in DNA isolated from peripheral lymphocytes, determined by HPLC with electrochemical detection; 8-OHdG excreted in urine, measured by ELISA; malondialdehyde (MDA) in urine, measured by fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
2
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(81 citation statements)
references
References 23 publications
5
72
2
2
Order By: Relevance
“…Our findings suggesting that increased intake of fruits and vegetables is associated with reduced oxidative stress are supported by some controlled feeding trials (20) but not others (38,39). In a study conducted among 28 women assessed to be at greater risk for breast cancer than the general population, Thompson et al (20) showed a significant inverse relationship between increased fruit and vegetable intake during a 14-day intervention and change in urinary 8-iso-PGF2a.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Our findings suggesting that increased intake of fruits and vegetables is associated with reduced oxidative stress are supported by some controlled feeding trials (20) but not others (38,39). In a study conducted among 28 women assessed to be at greater risk for breast cancer than the general population, Thompson et al (20) showed a significant inverse relationship between increased fruit and vegetable intake during a 14-day intervention and change in urinary 8-iso-PGF2a.…”
Section: Discussionsupporting
confidence: 62%
“…Higher intake of carotenoid-rich fruit and vegetables has been associated with a significant reduction in oxidative stress biomarkers, both in relation to DNA damage and lipid peroxidation (18)(19)(20). Diets low in antioxidants, particularly antioxidant carotenoids provided as vegetables and fruit in the diet, may contribute to increased oxidative stress (20,21) and thus indirectly contribute to breast cancer recurrence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the foodstuffs used in this study were rich in antioxidant. It has been reported that a diet antioxidant and fruites may have an antioxidant effects (Fan WY et al, 2000;Pool-Zobel et al, 1997;Thompson et al, 1999;Verhagen et al, 1997). A complex combination of these mechanisms might relate to the present results.…”
Section: Discussionsupporting
confidence: 50%
“…Bihar has notified forest area of 6,764.14 sq km, which is 7.1% of its geographical area (Department of Agriculture Gov of Bihar). Popular advice for healthy diets that may promote health and longevity include the daily consumption of at least three servings of fruits or vegetables and the variation of foods which are derived from different plants belonging to different botanical families (Thompson et al, 1999). Since, 2012 introduction of soybean in Begusarai district led to a shift in cropping system during rainy season from rice -wheat, rice -maize, maize -maize to soybeanwheat, soybean -maize system.…”
Section: Issn: 2319-7706 Volume 7 Number 02 (2018)mentioning
confidence: 99%